Fabrication of Oxide‐Dispersion‐Strengthened Ferritic Alloys by Mechanical Alloying Using Pre‐Alloyed Powder. Issue 8 (10th April 2022) - Zhang, Peng; Xu, Boyang; Zhao, Jianquan; Yin, Shengming; Yan, Youwei; Zhao, Mi
Abstract : Mechanical alloying (MA) is widely used to produce oxide‐dispersion‐strengthened (ODS) steels, which are potential candidate structural materials for the next‐generation fusion reactors. Here in this study, two kinds of ODS ferritic alloys, labeled A and B, are prepared through MA, followed by spark plasma sintering (SPS) and annealing. To prepare Alloy A, Fe powder, YH2 powder, and TiO2 powder are mixed for MA. To prepare Alloy B, a pre‐alloyed Fe–Cr–W–Y powder is first obtained by gas‐atomization, after which TiO2 powder is added for MA. Compared with the traditional MA method, where the highly stabilized Y2 O3 powder is usually selected, the use of TiO2 powder successfully reduces the milling time since it should be more easily decomposed and dissolved into the ferrite matrix. Some TiO2 –Y2 TiO5 duplex oxide particles of about 50 nm are found to generate through diffusion‐induced in situ reactions in Alloy A. In Alloy B, in contrast, a high number density of well‐distributed Y2 O3 particles of about 20 nm and ultrafine Y2 Ti2 O7 particles within 10 nm are observed. These nanoparticles maintain good coherent interfaces with the matrix, suggesting the precipitation mechanism. Herein, a new route for the efficient fabrication of ODS alloys is provided. Abstract : Herein this research, oxide‐dispersion‐strengthened ferritic alloys are prepared through mechanical alloying using TiO2 powder as an oxygen source rather than the commonly chosen Y2 O3 powder. The milling time is reduced due to the lower thermal stability of TiO2 compared with Y2 O3 . The use of Y‐containing pre‐alloyed powder further improves the efficiency of mechanical alloying.